The Influence of Business Strategy and Proactiveness on The Marketing Performance of Kelulut Honey on Msmes in Banjarmasin - Sulastini, Sulastini; Maskur, Maskur; Husnurrofiq, Husnurrofiq; Surya, Adhi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The background is the Marketing Performance of MSMEs. Currently, many problems arise related to the Marketing Performance of MSMEs. Therefore, problems related to performance need to find a solution. Focus on two issues, namely (1) Is there an influence of Business Strategy on MSME Marketing performance, and (2) Is there a Proactive influence on MSME Marketing performance. Research conducted on companies includes Anttila J., Jussila K., 2018, Ramayah T., The long-term objectives of previous research have focused on Business Strategy and Proactivity issues regarding Marketing Performance. Meanwhile, this research focuses on research conducted in Banjarmasin MSMEs. Specific targets to be achieved. Analyze and determine the influence of partially significant Business and Proactive Strategy on MSME Marketing Performance. Analyze and determine the influence of partially significant Proactive Strategy on MSME Marketing Performance. Based on the researcher's observations, the problem is that the Business Strategy and Proactivity in MSME Marketing Performance are not yet optimal. This research method uses a quantitative approach. The number of samples taken was 48 respondents using a saturated sampling technique. The data collection technique uses a questionnaire, while data analysis uses Smart PLS. The results of the research show that there is a significant influence of Business Strategy (X1), on the marketing performance of MSMEs. And there is a significant influence of Proactivity (X2), on the marketing performance of MSMEs. This research is explanatory research, namely testing the influence between Business Strategy variables. (X1), Proactive (X2), while the dependent variable is MSME Marketing Performance (Y), Data collection techniques used by researchers, namely Interviews, Questionnaires, Documentation. and Hypothesis Testing The proposed activity plan in the research aims to provide information that better interactions and relationships are actually a side effect of providing space for MSMEs to be competitive and proactive while still being able to accommodate existing problems.